Perturbações da matéria num modelo cosmológico com interações no setor escuro - Fuño, Alonso Romero (2014)
Interactions in the dark sector change the cosmological standard dynamic. In particular, they can be relevant to alleviate the problem of coincidence. In this thesis we study a cosmological model in which dark matter and dark energy interact in such a way that the ratio between the densities of the energies obeys a power law with respect to the scale factor. This model was introduced in the literature to address the problem of coincidence and the dynamics of the homogeneous and isotropic background has been studied in previous works. The present work extends this model to include deviations from homogeneity in the Universe. Small perturbations of homogeneity may grow due to gravitational instability to finally form the structures that we observe today. While these inhomogeneities are small, their growth can be studied by a perturbation theory of first order. We did a study of this perturbative dynamics both at the Newtonian and the relativistic levels. On the other hand, we actualize previous studies of the background dynamics by taking into account the most recent SNIa data. Basically, the model is tested against data from type Ia supernovae samples of SDSS, Constitution and Union 2.1. Within a simplified Newtonian theory we study the influence of the coupling between matter and dark energy on the dynamics of matter perturbations. On the basis of a relativistic gauge invariant theory we calculate the power spectrum of the matter and confront the results with data from the large-scale structure of the 2dFGRS and SDSS DR7 projects. Moreover, we perform a joint analysis of the background level with the perturbative level